Effect Of Bypass Fat Supplementation on Growth, Onset of Puberty, Biochemical Metabolites and Reproductive Parameters in Jersey Crossbred Prepubertal Heifers - Debbarma, Kinkar (Indian Journal of Animal Nutrition, 2021)
Bypass fat can increase the energy density of ration without having any adverse effects on feed intake and digestion. The experiment was conducted to investigate the effects of supplementation of bypass fat on the onset of puberty in dairy heifers. The trial was conducted with 12 prepubertal divided into control (C) and Treatment (T) groups. The ration for the experimental animals in control group were not supplemented with bypass fat, whereas heifers in treatment group received bypass fat at 50g/day/h for a period of 150 days. Bypass fat supplementation significantly (P<0.05) improved the mean live body weight, body condition score (BCS) and body fat thickness (BFT) in supplemented heifers. Bypass fat supplementation had no significant (P>0.05) effect on the proportion of heifers attaining puberty (50.00 vs. 33.33%) as well as the age at onset of puberty (605.67Â±22.67 vs. 626.50Â±28.50 days). There was no significant (P>0.05) difference observed between the control and treatment groups in the mean size of dominant follicle, CL and ovary. The overall mean uterine horn diameter during the trial period was significantly (P<0.05) higher in bypass supplemented group than in control group. The number of small, medium and large follicles did not vary between groups (P>0.05) in heifers during the study period. No significant (P>0.05) effect on plasma NEFA level was observed, however plasma glucose level was significantly (P<0.05) higher in bypass fat supplemented heifers. Hence, it can be concluded that bypass fat supplementation at 50g/day/h improved the body growth of supplemented heifers but did not have any beneficial effect on onset of puberty in heifers.